2020
DOI: 10.1155/2020/4508374
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of 13 Constituents of Radix Polygoni Multiflori in Rat Plasma and Its Application in a Pharmacokinetic Study

Abstract: Radix Polygoni Multiflori (RPM) has been widely used to treat various diseases in Asian countries for many centuries. Although, stilbenes and anthraquinones, two major components of RPM, show various bioactive effects, it has been speculated that the idiosyncratic hepatotoxicity induced by RPM may be related to these constituents. However, information on the pharmacokinetics of stilbenes and anthraquinones at a subtoxic dose of RPM is limited. A simple and sensitive UPLC-MS/MS bioanalytical method for the simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Radix Polygoni multiflori (root tubers of PMT) is mostly used in treating many kinds of diseases, such as rubella, scrofula, waist and knee pain, paralysis, vaginal discharge, hypercholesterolemia (liver and kidney), malaria, and various other diseases, possessing neuro-protective, antioxidation, immunomodulation, anti-hyperlipidemia, anticancer, heap-toprotection, anti-inflammation, and anti-CoV functions [ 86 , 87 , 246 ]. The potent bioactive compounds present in PMT which are responsible for the therapeutic effects against various diseases are listed in Table 1 [ 84 , 85 , 88 , 247 ]. However, Ho et al found that emodin is the most effective compound against SARS-CoV-1.…”
Section: Known Medicinal Plants Acting On Ace-2 Receptormentioning
confidence: 99%
“…Radix Polygoni multiflori (root tubers of PMT) is mostly used in treating many kinds of diseases, such as rubella, scrofula, waist and knee pain, paralysis, vaginal discharge, hypercholesterolemia (liver and kidney), malaria, and various other diseases, possessing neuro-protective, antioxidation, immunomodulation, anti-hyperlipidemia, anticancer, heap-toprotection, anti-inflammation, and anti-CoV functions [ 86 , 87 , 246 ]. The potent bioactive compounds present in PMT which are responsible for the therapeutic effects against various diseases are listed in Table 1 [ 84 , 85 , 88 , 247 ]. However, Ho et al found that emodin is the most effective compound against SARS-CoV-1.…”
Section: Known Medicinal Plants Acting On Ace-2 Receptormentioning
confidence: 99%
“…Even at higher doses (82.4 mg/kg), the levels of emodin detected in vivo remained very low. The appearance of glucuronidation metabolism and oxidative conversion into rhein may be the main reasons for the extremely poor oral bioavailability of emodin (Liu et al, 2012;Li et al, 2017;Cheng et al, 2020). Li et al (2019) revealed that the absorption of emodin was faster, and the effect was rapider when used in combination with aloeemodin, rhein, chrysophanol, or physcion.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…With the doses decreasing from 40 g/kg to 10 g/kg and 20 g/kg, oxyresveratrol and rhein became undetectable in plasma [ 25 ]. The pharmacokinetic parameters indicated that the absorption and elimination of these major components were generally fast with time to maximum plasma concentration (T max ) less than 2 h for TSG, emodin, and physcion, and half-lives of these three compounds ranged from 0.18 to 8.37 h after a single dose of RPM extracts orally administrated to SD rats [ 25 , 27 , 30 , 31 , 32 ]. Since the area under the concentration-time curve (AUC) and peak concentration (C max ) of TSG and emodin increased linearly along with the dose of RPM extract increasing from 10 g/kg (TSG: 327.9 mg/kg, emodin: 5.6 mg/kg) to 40 g/kg (TSG: 1312.0 mg/kg, emodin: 22.3 mg/kg), linear pharmacokinetics of TSG, and after single oral administration of RPM extracts in rats, were suggested [ 25 ].…”
Section: Pharmacokinetics Of Rpmmentioning
confidence: 99%